Experimental Study of Transmission Characteristics of a Disk Drive's Vibration Characteristics of a Disk Drive's Vibration. (November 2014) - Chiu, Min-Chie; Chang, Ying-Chun
Presently, there is a trend to design larger capacity hard disks that have a faster revolving speed and a precise mechanism. However, because of external vibrations, these are highly sensitive to data transmission. Therefore, vibration control on hard disks is crucially important. In this paper, a traditional hard disk is placed on a vibration testing device. Data transmission efficiency for the disk will be detected via IOmeter software. Here, the influence of a traditional hard disk's data transmission with respect to external forces (various vibration accelerations), revolving speeds, tilted angles, hardness and thickness of damping material, and material property will be experimentally assessed. Results reveal that a slight tilted angle will result in better data transmission. In addition, the hardness of the hard disk plays an essential role in reducing the vibrational impact on the data transmission. Also, data transmission in the damping material of the shoe cushion will be more efficient than that of a pneumatic cushion. Moreover, the data transmission will decrease when the rotating speed of the disk increases. Consequently, the thickness of the damping material will influence the data transmission even though the hardness is fixed.